2018
DOI: 10.1177/1941738118816282
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Ankle Syndesmotic Injury: A Systematic Review

Abstract: Context:Ankle syndesmotic injuries present a significant challenge for athletes due to prolonged disability and recovery periods. The optimal management of these injuries and rates of return to sport in athletes remains unclear.Objective:The purpose of this study was to evaluate return to sport for athletes after ankle syndesmotic injuries.Data Source:The electronic databases MEDLINE, EMBASE, and PubMed were searched for relevant studies from database inception to January 15, 2017, and pertinent data were abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 20 publications
1
29
2
Order By: Relevance
“…A systematic review and meta-analysis evaluated 48 studies with a total of 5770 subjects and reported that 63% of individuals returned to preinjury activity levels after anterior cruciate ligament reconstruction surgery [ 46 ]. Moreover, a systematic review evaluated 10 studies with 312 patients and reported that the rate of return to preinjury activity level after syndesmotic ankle injuries was 93.8% [ 47 ]. As in the study above, no difference in the impact variables and the lower extremity strength was found between groups by performing the jumping kick after complete recovery from injury.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis evaluated 48 studies with a total of 5770 subjects and reported that 63% of individuals returned to preinjury activity levels after anterior cruciate ligament reconstruction surgery [ 46 ]. Moreover, a systematic review evaluated 10 studies with 312 patients and reported that the rate of return to preinjury activity level after syndesmotic ankle injuries was 93.8% [ 47 ]. As in the study above, no difference in the impact variables and the lower extremity strength was found between groups by performing the jumping kick after complete recovery from injury.…”
Section: Discussionmentioning
confidence: 99%
“…3 Syndesmosis injuries can present with various obstacles during the rehabilitation process, including prolonged disability, recovery periods, and uncertainty regarding the ideal treatment approach. [4][5][6] There are several surgical options to consider in maintaining the structural integrity of the ankle joint after a grade II or higher syndesmosis injury has occurred. The current "gold standard" is the metallic syndesmotic screw.…”
Section: Clinical Scenariomentioning
confidence: 99%
“…PubMed, SportDiscus, and Google Scholar were searched, as well as reference lists, which resulted in 5 articles relating to the efficacy of utilizing the TightRope ™ surgical procedure in the treatment of syndesmosis injuries. [2][3][4]7,9 The search was limited to articles published within the last 10 years. Two randomized control trials and one cohort study comparing the TightRope ™ procedure with a metallic syndesmotic screw met the inclusion requirements and were utilized.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
See 2 more Smart Citations